Maximizing the neuroprotection from Citrus aurantium leaves: Optimization of a blended extract from a sequential extraction process with compressed fluids and NADES - Victor M. Amador-Luna; Miguel Herrero; Marta Jiménez de la Parra; Ángel Gómez Arribas; Elena Ibáñez; Lidia Montero (Advances in Sample Preparation)
Citrus aurantium, also known as bitter orange, and the by-products obtained during its processing are a rich source of bioactive compounds. In particular, leaves from the tree pruning and from fruits harvesting are considered an agrifood-related waste with high valorization potential. Considering the wide variety of bioactive compounds present in the leaves (carotenoids, terpenes and phenolic compounds), this study is focused on the valorization of C. aurantium pruning waste through a sequential three-step extraction process using green extraction techniques, i.e. supercritical fluid extraction (SFE), followed by pressurized liquid extraction (PLE) using natural deep eutectic solvents (NADES), and an antisolvent extraction to recover the remaining bioactive compounds adsorbed to the NADES and extraction residues. In this sense, this is the first time that PLE using NADES followed by an antisolvent step to re-extract the compounds from the PLE residue is presented. Moreover, different protocols to efficiently remove the NADES from the PLE extract were also studied for the first time. Due to the different nature and bioactivity of the obtained extracts, the mixture of the three fractions was optimized to enhance its overall preventive potential against neurodegenerative diseases. Finally, its scalability to a semi-pilot scale was evaluated, giving rise to increased bioactive values of the blended extract.